Courting disaster : how the Supreme Court is usurping the power of Congress and the people - Robertson, Pat. (Nashville : Integrity Publishers, 2004)
The End of American Democracy "Concentration of power is what always precedes destruction of human liberties." Woodrow Wilson "An out-of-control judiciary is the single greatest threat to democracy and the religious and moral foundations of America," says Pat Robertson. In this no-holds-barred look at American justice, Robertson examines the dangers of a culture with "no judicial limits" and shows how the rewriting of Constitution by liberal justices is steadily eroding the power of representative government -- and democracy itself. This landmark work also considers the alarming spiritual implications of justice run amok. From the increased hostility toward religion to the destruction of sexual standards and the assault on the sacred institution of marriage, this eye-opening book examines the devastating effects of judiciary that is out of control. Robertson makes a compelling case that judicial activism is the pivotal issue of our time, and calls for concerned citizens all over America to pay attention to what's happening in their courts and to take a stand before it is too late.
The end of American democracy -- The original intent of the founders -- Defying the will of the people -- The court's liberal agenda -- Prayer and Bible reading -- Free speech and equal rights -- The dignity of human life -- Honoring our heritage -- Our black-robed masters -- A nation at war -- To restore justice -- The path to victory.
Includes bibliographical references and index.
Keywords: Christianity and politics -- United States -- History; Christianity and law; History